THE CHARACTERISTICS OF ARTIFICIAL RICE WITH SEAWEED Eucheuma cottonii ADDITION AS A DIETARY FIBER SOURCE - Natalia Prodiana Setiawati; Joko Santoso; Sri Purwaningsih (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
The utilization of local food commodities such as corn and cassava with seaweed addition as a dietary fiber source for producing artificial rice through extrusion technology is an  alternative for food diversification. The research was carried out to find out the best composition (rice, corn, cassava, and seaweed) and temperature of extrusion process on making artificial rice and the influence of dietary fibre on sensory properties and physicochemical. The composition of rice, corn, and cassava in proportion  of 1:3:1 with 20% seaweed, Eucheuma cottonii, addition and temperature extruder of 90 °C were selected as the best product for artificial rice. The  sensory evaluation was 8.02±0.21 (people’s preference). In physicochemical properties, dietary fiber significantly affected on low bulk density and starch digestibility. This condition is very good for health especially in maintaining the stability of blood glucose in the body. Keywords: artificial rice, composition, extrusion, seaweed, dietary fibre, temperature